2001
DOI: 10.1108/02651330110381998
|View full text |Cite
|
Sign up to set email alerts
|

An integrative framework for cross‐cultural consumer behavior

Abstract: The world economy is becoming increasingly cross-cultural. During the next decades, as marketers enter new international markets, an understanding of how culture influences consumer behavior will be crucial for both managers and consumer researchers. This article presents a framework that integrates and reinterprets current research in cross-cultural consumer behavior. The framework also serves to identify areas that need further research and can be used as a template for marketers seeking to understand their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
186
1
18

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(207 citation statements)
references
References 64 publications
2
186
1
18
Order By: Relevance
“…Examples include personality, social processes and mental processes [16]. There are two types of approaches to analyzing culture, including etic approaches and emic approaches [18]. Etic approaches define culture as "the collective programming of the mind which distinguishes the members of one group or category of people from another" [19].…”
Section: Cross-cultural Study Of Consumer Behaviorsmentioning
confidence: 99%
“…Examples include personality, social processes and mental processes [16]. There are two types of approaches to analyzing culture, including etic approaches and emic approaches [18]. Etic approaches define culture as "the collective programming of the mind which distinguishes the members of one group or category of people from another" [19].…”
Section: Cross-cultural Study Of Consumer Behaviorsmentioning
confidence: 99%
“…As a result, values persist over time and, therefore, may have an influence on the way consumers behave. This further influences the choices that individuals make regarding consumer decisions from everyday products to major or important purchases (Luna & Gupta, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…The cultural value system includes cultural elements that people have in common with the group to which they belong, as well as idiosyncratic values unique to that individual (Luna & Gupta, 2001). Societal culture, as well as regional subculture and familial values, all influence the formation of an individual's cultural values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of studies that have investigated ethnic influences in an Asian setting. This is surprising at a time when marketing scholars make continuous pleas for cross-national studies and emphasize the acute need for international research to establish the universality of consumer behavior concepts and theories (Lee & Green, 1991;Luna & Gupta, 2001;Odgen, Odgen, & Schau, 2004). The study reported in this article responds to these calls and extends the research stream into Malaysia.…”
Section: Introductionmentioning
confidence: 99%